Problems and successes in the combined application of the Ilizarov and Masquelet technologies - Dmitry Yu. Borzunov; Denis S. Mokhovikov; Sergey N. Kolchin; Sergey V. Lyulin; Sergei M. Kutepov; Rinat T. Gilmanov (Гений oртопедии, 2022)
Introduction Based on the assessment of the problems and effectiveness in the use of the induced membrane and bone transport techniques, a new technological solution was proposed. It combines the methods of Masquelet and Ilizarov for restorative treatment of patients with bone defects and nonunion. Materials and methods The combination of the technologies was successfully applied for filling bone defects in the conditions of active purulent infection and its remission in 24 patients. Patients of the first group (n = 17) had bone defects in the conditions of the osteomyelitic process remission. In the second group of patients (n = 7), the osteomyelitic process was active. The combined technology of bone grafting included segment reconstruction in two stages. At the first stage of treatment, a sanitizing treatment of soft and bone tissues in the area of the defect and nonunion was performed followed by spacer implantation and transosseous fixation of bone fragments with the Ilizarov apparatus. During the second operating session, the spacer was removed, and after osteotomy (corticotomy), the fragment(s) were transported according to Ilizarov. Empirical antibiotic therapy against a wide range of pathogens was started after the verification of the microbial tests of the biomaterial and the determination of sensitivity to antibiotics, the correction of antibiotic therapy was carried out. Results The postoperative wounds in the area of the implanted spacers healed by primary intention in the first group. In two patients of the second group (29 %), purulent fistulas were formed by the time the spacers were removed, and the wounds healed by secondary intention. The duration of distraction in the first group was 45.4 ± 9.8 days. Bone transport in the patients of the second group continued 52.8 ± 5.3 days. The duration of fixation of the segments with the device was 195.1 ± 9.9 days in the first group and 181.8 ± 11.4 days in the second group. Discussion At the initial stage of the combination of the Masquelet technique and non-free Ilizarov bone grafting, the risks of the activity of a purulent process remain if the debridement of the infection nidus is not radical, implanted spacers with a prophylactic dose of antibiotics are massive, and the antibiotic therapy is empirical. The formation of an induced membrane with bactericidal activity at the second stage of surgical treatment, the creation of favorable conditions for bone transport, adequate sanitation of the purulent focus, and targeted antibiotic therapy ensure a stable suppression of the activity of the purulent process. Conclusions Surgical rehabilitation of patients with segmental infected defects results in bone defect filling with distraction regenerates undergoing complete organotypic restructuring, which eliminates the likelihood of deformities or fractures at the level of newly formed bone areas and reduces the risk of recurrence of the osteomyelitis process.